Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Ubur-Ubur Berantai Terhadap Kemampuan Numerasi Siswa Materi Statistika Kelas VI SD Negeri 091270 AFD 13 Laras - Delima Krisdayanty Simangunsong; Aprido Bernando Simamaora; Sukardo Sitohang (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of the Problem Based Learning learning model assisted by Chained Jellyfish Media on Students' Numeracy Ability in Class VI Statistics Material at State Elementary School 091270 AFD 13 Laras.The type of research used in this research is experimental research. Research based on one group pretest posttest design. The sample for this research was 23 class IV students. The sampling technique in this research is nonprobability sampling. The data collection technique in this research uses a test in the form of multiple choice questions which has four choices, namely a b c and d with a total of 15 questions.Based on the level homogeneity test, the yield value was 0.890. According to the criteria that have been determined: if the value of the variation is >0.05 then the data is declared to contain uniform variations. In the event that the results show that 0.890 is >0.05, it can be concluded that the data obtained contain the same or homogeneous characteristics. The normality test and homogeneity test have been completed and have been continued with the hilpotelsils test. The T-test results obtained by the students were 15.760 and 2.074. Delngan delmilkan > which means HO rejected and Ha diltelrilma. From the training results data obtained, it is clear that there is an influence of the Baseld Learnil Problem Learning Model assisted by the Belrantail Jellyfish Meldila on students' numerical abilities.